Figurative Potential of Russian Hydronymes in the Poetry of 19th – 20th Centuries - Gizatullina, Azaliya R.; Hayrutdinova, Gulshat A. (Journal of History Culture and Art Research, 2017)
The article studies the peculiarities of Dnieper, Don, Volga and Neva hydronyms use as aesthetically significant elements of an artistic text. The urgency of the work is that the development of language and speech aesthetics issues are among the promising trends of linguistic studies. However, the aesthetic resources of most onomastic units, including toponyms, are still poorly studied. The purpose of this study is to analyze the figurative possibilities of these hydronyms, functioning in the poetic works of Russian authors. The following methods were used as the main ones in the work: modeling, distributive, semantic-stylistic and quantitative analysis. The material for the study was represented by the poetic works of the 19-20th centuries, extracted from the "National Corpus of the Russian Language". The novelty of the work was made up of selected figurative paradigms, in which the considered hydronyms are used as the subject of comparison. During the performed study five most voluminous figurative paradigms were revealed, in which the position of the right member is replaced by lexical units related to the concepts of "being", "water", "substance", "tissue" and "terrestrial space". The criteria of intentional rapprochement of hydronyms with other subject lexemes were determined in order to develop the imagery of a poetic text. The findings can be used to study the onomastic space of Russian language, as well as for the further development of artistic speech theory.